The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyg.2020.02200
|View full text |Cite
|
Sign up to set email alerts
|

An Actual Natural Setting Improves Mood Better Than Its Virtual Counterpart: A Meta-Analysis of Experimental Data

Abstract: Accumulating evidence indicates that simulated natural settings can engage mechanisms that promote health. Simulations offer alternatives to actual natural settings for populations unable to travel outdoors safely; however, few studies have contrasted the effects of simulations of natural settings to their actual outdoor counterparts. We compared the impacts of simulated and actual natural settings on positive and negative affect (mood) levels using a pooled sample of participants enrolled in extant experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 76 publications
2
54
0
1
Order By: Relevance
“…For example ( Anderson et al, 2017 ; Browning, Mimnaugh, et al, 2020 ) both showed stronger effects of nature 360-VR on negative than positive affect, and ( Chirico & Gaggioli, 2019 ) found that 360-VR reduced sadness to a greater extent than even real nature. A recent meta-analysis showed that positive affect only increased in real (but not simulated) natural settings, whereas negative affect improved to a similar extent in both contexts ( Browning et al, 2020 ). Browning and colleagues have explored possible reasons for this, including the idea that being “sealed in” to VR nature by way of a HMD may provide a greater opportunity to escape negative thoughts and excessive cognitive demands, allowing for faster and more complete recovery of attentional processes, and associated reduction in negative affect ( Browning, Mimnaugh, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example ( Anderson et al, 2017 ; Browning, Mimnaugh, et al, 2020 ) both showed stronger effects of nature 360-VR on negative than positive affect, and ( Chirico & Gaggioli, 2019 ) found that 360-VR reduced sadness to a greater extent than even real nature. A recent meta-analysis showed that positive affect only increased in real (but not simulated) natural settings, whereas negative affect improved to a similar extent in both contexts ( Browning et al, 2020 ). Browning and colleagues have explored possible reasons for this, including the idea that being “sealed in” to VR nature by way of a HMD may provide a greater opportunity to escape negative thoughts and excessive cognitive demands, allowing for faster and more complete recovery of attentional processes, and associated reduction in negative affect ( Browning, Mimnaugh, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…While we encourage researchers to make use of this technology in experimental design to enhance methodological rigor, we also warn about challenges associated with this technology. While VR and IVE technology can provide more vivid experiences of nature as compared to non-immersive virtual exposure (e.g., videos or pictures), recent analyses show that exposure to virtual nature provides psychological responses to a lesser extent than real nature (Browning et al, 2020). This needs to be taken into account when interpreting findings of experiments using environmental exposure via VR or IVE.…”
Section: Recommendationsmentioning
confidence: 99%
“…Some further evidence suggests that being exposed to real green and blue space induces psychophysiological and behavioral responses that can be differentiated from those induced by the same environments when reproduced by visual media (Huang, 2009;Huang et al, 2019). Similarly, a recent meta-analysis showed that real natural settings benefit mood to a greater degree than simulated settings (Browning et al, 2020).…”
Section: Green Space Exposure Is Related To Reduced Psychosis Riskmentioning
confidence: 99%